Pt–Cu bimetallic nanoparticles synthesized by polyol method under different reduction conditions - Mohd Husin, Mohd Haizal; Mohd Ridzuan, Nordin; Imran Syakir, Mohamad; liew, kong yong (2014)
Platinum–copper (molar ratio 1:1) bimetallic nanoparticles were synthesized by polyol method using ethylene glycol (EG) as the solvent and PVP as the stabilisation agent under microwave conditions compare with reduction by using NaBH4 at room temperature and combination both technique of reduction. The samples were characterised by UVvis, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron (XPS). UV-vis results show that formation of particles from colloid Pt-Cu bimetallic samples. TEM analyses confirm that the very fine and monodisperse with narrow size distribution particle with average particle size were 3.1 ± 1.0 nm for combination reduction technique, 3.3 ± 0.8 nm for microwave reduction and 4.1 ± 1.1 nm for NaBH4 reduction. XRD results show that there is no peak in the pattern of bimetallic nanoparticles observed unless peak of carbon refer to PVP carbon content. However XPS illustrates resulted that both elements in the nanoparticles are obtain based on characteristic metallic binding energy. Moreover, besides the influencing of sizes Pt-Cu bimetallic nanoparticles due to technique of reduction, it is also influence the Pt to Cu atomic ratio whereas 1:2, 1:1.3 and 1:1.7 respective to Pt-Cu (1:1)-mw; Pt-Cu (1:1)-NaBH4 and Pt-Cu (1:1)-comb.